Atherfieldastacus magnus (MʼCoy, 1849), a widely distributed crustacean during Early Cretaceous (Valanginian-Albian) times. (November 2019) - González-León, Oscar; Moreno-Bedmar, Josep A.; Gómez-Cruz, Arley de Jesús; Bermúdez, Hermann D.; Moreno-Sánchez, Mario; Vega-Sandoval, Francisco A.; Vega, Francisco J.
Abstract: Several specimens of the mecochirid lobster Atherfieldastacus magnus (MʼCoy, 1849) collected in Mexico and Colombia, represent the oldest record for this species. The Mexican specimens are from the Valanginian-Hauterivian San Juan Raya Formation, in Puebla, central Mexico, and the Colombian specimens were found in Barremian deposits of the Paja Formation, north of Bogotá. Previous reports of Atherfieldastacus magnus include numerous specimens from the Aptian of Europe (UK, Spain), Mexico, Colombia and Tibet. The new specimens collected in shales of the San Juan Raya Formation of Mexico, represent diverse sizes and excellent quality of preservation; in some samples the articles of the antennae can be observed, among other morphological characters not reported previously for this species. The association of the Mexican specimens with mollusks, echinoids and cones of an araucaria gymnosperm, suggest a shallow marine environment. The same is observed for the Colombian specimens, where sediments of the Paja Formation are reported as shallow marine. Additionally, sexual dimorphism in A. magnus is recognized, based on the analysis of differential morphology of the pleurae. Thus, for the moment, the biostratigraphic range for A . magnus ranges from the Valanginian to the Albian (Early Cretaceous), with the oldest occurrence in Mexico, where it persisted until Aptian times. Highlights: Oldest record of a species of Cretaceous lobster with a very wide paleogeographic distribution during early Cretaceous. Juvenile assemblage and confirmation of sexual dimorphism. New localities for this species, reported from Mexico and Colombia. Unique preservation that allows to see, for first time, delicate morphological features of this species. Correction of the age for an important Lower Cretaceous litostratigraphic unit of Mexico (San Juan Raya Formation). Numerous specimens illustrated in order to show every morphological detail. A shallow marine paleoenvironment interpreted for the studied lithostratigraphic units of Mexico and Colombia.